1997
DOI: 10.1021/bi961955q
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and Phosphorylation Change the Oligomeric Structure of Phospholamban in Lipid Bilayers

Abstract: Phospholamban (PLB), a 52-residue protein integral to the cardiac sarcoplasmic reticulum, is a key regulator of the Ca pump. PLB has been shown to form pentamers in the denaturing detergent sodium dodecyl sulfate (SDS), but its oligomeric state in the natural environment of the lipid membrane remains unknown. In order to address this issue, we performed electron paramagnetic resonance (EPR) experiments on two types of lipid-reconstituted, recombinant PLB: wild type (WT PLB) and a mutant substituted with alanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
241
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(274 citation statements)
references
References 44 publications
26
241
7
Order By: Relevance
“…To examine this issue, SERCA2a was co-expressed with L37A-PLB, which is monomeric on SDS-PAGE (17) and, more importantly, also when reconstituted in lipid membranes (19). Surprisingly, we observed that L37A-PLB was a more effective suppressor of SERCA2a Ca 2ϩ affinity than wild-type phospholamban.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…To examine this issue, SERCA2a was co-expressed with L37A-PLB, which is monomeric on SDS-PAGE (17) and, more importantly, also when reconstituted in lipid membranes (19). Surprisingly, we observed that L37A-PLB was a more effective suppressor of SERCA2a Ca 2ϩ affinity than wild-type phospholamban.…”
Section: Discussionmentioning
confidence: 92%
“…Microsomes isolated from infected Sf21 cells exhibit high levels of ATP hydrolysis and active Ca 2ϩ transport, and, furthermore, cardiac-like coupling between phospholamban and SERCA2a is retained. With the baculovirus system, we also demonstrate that a monomerforming mutant of phospholamban (17,19), unexpectedly, is a stronger inhibitor of SERCA2a activity than is the pentamer, suggesting that the monomer may be the key molecular species regulating the Ca 2ϩ pump in sarcoplasmic reticulum membranes. No evidence for a Ca 2ϩ channel activity of phospholamban was obtained.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…M13 MCP is composed of a single transmembrane segment and as such is expected to immobilize around 10–12 phospholipids in its immediate vicinity or annular binding sites (Marsh and Horváth 1998; Cornea et al. 1997). However, due to MCP aggregation, only five annular binding sites were identified by protein molecule when using ESR (Wolfs et al.…”
Section: Fret Analysis Including Contributions From Bulk Acceptorsmentioning
confidence: 99%